Institutional quality, cyclicality of macroeconomic policies and the effects of macroeconomic shocks: Evidence from transition economies - Shaig Adigozalov; Vugar Rahimov (Graduate Institute of International and Development Studies, 2015)
In this paper, we study the role of institutional quality in the cyclicality of macroeconomic policies of transition economies. Using annual data over 1996-2013, we find that the quality of institutions play a significant role in their ability to carry out counter-cyclical macroeconomic policy. This paper also analyzes the effects of monetary and fiscal shocks on output. Dividing the countries into two groups, namely CIS and non-CIS, we find that median impulse response of CIS countries GDP to monetary shock is negative, while in non-CIS countries this effect is close to zero. However, we find negative effect of fiscal shock on CIS countries' GDP while the median effect of fiscal shock on GDP is very close to zero in non-CIS countries.
Keywords: 330; institutional quality; transition economies; macroeconomic policies; monetary; shocks; fiscal shocks